Association of Early Postoperative Peripancreatic Drainage Fluid Culture with Postoperative Pancreatic Fistula (POPF) and Antibiogram After Pancreaticoduodenectomy (PD) to Assess the Outcome - Hoque, Md Rajibul; Quiyum, Md Abdul; Paul, Arun Kumar; Hassan, A Z Mohmudul; Azimuddin, Md (Journal of Surgical Sciences, 2022)
Background: Postoperative pancreatic fistula (POPF) after pancreaticoduodenectomy (PD) are often accompanied by perioperative bacterial contamination which may lead to abscess, MOF and death. However the impact of intra operative bacterial contamination on surgical outcome after PD has not been assessed in depth in our country. Aim of this study: To know the bacterial contamination and antibiogram at an earlier basis at the peripancreatic anastomotic area after PD and to assess their relation to the aggravation of POPF and septic complications. Materials and methods: Total 24 patients were enrolled who underwent PD.Drain fluid amylase level were measured on day 1, 3 and 7 postoperatively. Peripancreatic drain fluid culture was done on day 01. According to ISGPF criteria for POPF, patients who had three times elevated (>300 IU/ml) amylase on post operative drain fluid had been considered as Pancreatic Fistula. So all patients(N=24) were divided into two groups on the basis of drain fluid culture result. Group 1(n=14)- was patient with positive culture result, Group 2(n=10)- was patient with negative culture result. Result: The median age of 24 cases was 55years (range 32-69 years). There were 15 male and 9 female. The commonly found micro organisms in the PP drain fluid culture were Klebsiella alone 8 (57.14%) cases, E.coli 3 (21.60%)cases. Klebsiella with E.coli 1 (7%) case, with Enterobacter 1 (7%) case and Acenobacter alone in 1 (7%) case. 13 patients developed POPF (grade A/B/C) where 11 (84.6%) were C/S positive. Among them 9 developed Grade-A POPF and sensitive to colistin sulphate, meropenem, amoxiclav and linezolid. 1 was Grade B POPF and was sensitive only to colistin sulphate. 1 developed Grade C POPF, which was resistant to all the drugs and not survived eventually due to sepsis and MOF. Preoperative raised CRP level (> 20 mg/l) was found in 17 cases ( 70.83%) where 12 was C/S positive which was statistically significant. Pre operative biliary stenting was done in 11 patients where 8(77%) was culture positive with statistically significant result. The Dunking procedure was also found statistically significant to develop POPF along with C/S positive cases. Conclusion: Evidence of perioperative bacterial contamination has a strong predictive value in the development of grade-B/C POPF from grade-A where multi drug resistant polymicrobial agents may play an important role. Journal of Surgical Sciences (2022) Vol. 26(1) : 15-24